Development of pteridophyte catarium (herbarium catalog) media in plantae materials for X graders of SMA Islam Batu - Faqih Asshiddiqie; Mohamad Amin; Elly Purwanti; Atok Miftachul Hudha; Ahmad Fauzi (Universitas Muhammadiyah Malang, 2021)
: Plantae material is one of the materials that requires a direct observation process to determine the characteristics, morphology, metagenesis, and benefits for the environment, especially in Pteridophyte material. So far, students only use textbooks and students have not been invited to learn with contextual learning objects. Thus, media is needed to facilitate direct observation and identification of plants. The purpose of this research is to produce learning media Pteridophyte catarium (Catalog Herbarium). This type of research is research and development (R&D) with the ADDIE development model. The results showed that the quality of the product according to media experts was very feasible with an assessment percentage of 77.08%, as well as according to material experts who said it was very feasible with a 95% rating percentage. The results of the teacher's response were 79.16% and the results of readability by students on a small and large scale respectively were 76.5% and 81.16%, indicating very decent quality. It was concluded that the product in the form of Pteridophyte catarium learning media was very suitable to be used as a teacher's learning media in plantae biology learning activities.